Decision Determinants of Generation Z and Millennials in Paying ZIS Digital - Adela Putri Oktavia; Ekawaty, Marlina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the influence of perceived ease of use, perceived usefulness, trust, digital literacy, and religiosity on the decisions of millennials and Generation Z in West Java in making ZIS payments through digital platforms. The research method used is quantitative with binary logistic regression analysis techniques on 110 respondents selected through purposive sampling. The results of the study indicate that simultaneously, all five variables have a significant influence on the decision to make ZIS payments digitally. Partially, perceived ease of use, perceived usefulness, trust, and digital literacy were found to have a positive and significant influence on the decision to make ZIS payments through digital platforms. Meanwhile, religiosity has a negative and insignificant influence, indicating that the level of religiosity plays more of a role as a foundation that influences the decision to pay ZIS, but is not a determining factor in the choice of digital payment methods.